ENHANCEMENT SISTEM INFORMASI OFFICE DWIGITAL.ID GUNA MENINGKATKAN MONITORING PELANGGAN: Office Information System, CodeIgniter, Waterfall, WhatsApp API, Black Box Testing - Puad, Lailyn; Budiarti, Rike Limia; Nailah, Kholisah (JURNAL AKADEMIKA, 2025)
This research focuses on developing a web-based office information system for Dwigital.id (CV. Klik Anugerah Ciptareka) using the CodeIgniter framework to enhance internal work efficiency and accelerate customer interaction through WhatsApp API integration. The research employs a qualitative approach with the Waterfall development model, consisting of stages such as requirements analysis, system design, implementation, testing, and maintenance. The system includes main features such as CRUD Withdraw, CRUD Sales System, and Monitoring System integrated with WhatsApp for direct communication with customers. The testing process uses the Black Box Testing method to evaluate the functionality an reliability of each module. The results show that the system runs effectively and meets user needs, improving administrative performance and real-time customer engagement. The developed system is declared feasible for operational implementation and contributes to improving Dwigital.id digital service management.